Maqasid al-Shariah perspectives on the implementation of Hire-Purchase Act 1967 in Malaysia with reference to Al-Ijarah Thumma al-Bai' financing contract - Awang, Mohd Daud; Asutay, Mehmet (Malaysian Consumer and Family Economics Association, 2017)
This study aims to critically examine the meaning of the Al-Ijarah Thumma al-Bai' (AiTAB) contract and hire-purchase (HP) contract. It is also to explore several issues regarding the procedures of the Malaysian Hire-Purchase Act 1967 and it's contradiction to the Shariah. There are three main issues that were highlighted; transferring of ownership, right and liability, and charges. The Maqasid al-Shariah framework is a compatible approach for this study to solve these issues which does not only to harmonise both contracts but also in morally aspect. The findings of this study demonstrate how Maqasid al-Shariah should employ HP contract issues that might not be contradicted to AiTAB in developing a better understanding between AiTAB and HP practices as Islamic banking product.